The Praxis of Labour: A Pluralistic Approach to Value Theory in Ecological Economics - Youngman, Ben (Auckland University of Technology, 2024)
This thesis addresses challenges in quantifying environmental values and resources by advocating for an interpretive approach to ecological economics, embracing pluralism. The research question explores whether economic pluralism can enable new techniques for the valuation of human ecosystem benefits, focusing on ‘water purification’. Economic value theories are reviewed, highlighting limitations of the widely used Marginal Utility Theory and its applications in ecological economics. Alternative value theories, including Karl Marx’s labour theory of value, Praxeology and subjective value theory, and manahau as a Māori value theory, are proposed. Interpretivism is introduced as a necessary tool for economic pluralism, emphasising an open-minded approach to subjective variances. Freshwater ecosystems and ecological concepts are examined, emphasising freshwater metabolism as a key indicator for water quality and purification processes. Current freshwater valuation methods, predominantly relying on marginal utility theory, face challenges. The need for a value theory acknowledging context and subjectivity is underscored, with interpretivism as a crucial tool. The Praxis of Labour (PoL), a circular model grounded in praxeology, subjective value, and Marxian labour theory is introduced. The PoL’s applicability to ecological economic problems is discussed, offering arguments for greater accuracy in valuing environmental goods and services. Due to the ambitious scope of this thesis, the PoL is conceptually applied to a theoretical case study featuring a sheep and beef farmer named Barry, highlighting the necessity to map the conceptual space for the PoL framework before being grounded in the real-world, using actual data. The case-study conceptually illustrates how Barry’s engagement in water purification projects is valued based on labour units, considering downstream benefits. Political and systemic implications for public and private policy and decision-makers, such as private ownership accountability and the PoL’s potential in Environmental Social Governance (ESG) reporting, are discussed. Monitoring and evaluation, essential for fair resource distribution, are addressed under the PoL. Limitations, including anthropocentrism, resistance to change, and fundability, are acknowledged. Concluding thoughts highlight the need for a mandate incentivising environmentally friendly behaviours and charging extractive practices. The PoL is emphasised as a transparent tool for reporting individual values towards the environment. Future research directions include grounding the PoL in a real-world scenario, applying the PoL to other human ecosystem benefits, and incorporating interpretivism and subjective value arguments for a more culturally pluralistic understanding of value. Caution is highlighted on the generalisation of values that occurs when economic principles are applied to environmental contexts. Ultimately, the PoL is presented as a tool for navigating sustainable development in the face of global challenges.